At the Intersection Between Optics and mmWave Design: An Energy Autonomous 5G-Enabled Multilens-Based Broadbeam mmID for "Smart" Digital Twins Applications - Lynch, Charles A.; Soto-Valle, Genaro; Hester, Jimmy G. D.; Tentzeris, Manos M. (IEEE transactions on microwave theory and techniques, 2024)
For the first time, the authors propose a 5G/mmWave multilens-based retrodirective backscatter system capable of large coverage in both azimuth and elevation directions. The structure features two biconvex lenses backed by an array of individual backscattering elements (pixels). The components of the system are described in detail, including the cascaded polytetrafluoroethylene (PTFE) lenses and the pixel array. Subsequently, the entire system is assembled, and its detectability and large azimuth/elevation coverage is measured and compared to the state-of-the-art. The millimeter wave identification (mmID) displays a peak differential radar cross Section (RCS) of −15.7 dBsm with a −10 dB coverage of 2.244 sr about boresight, improving the angular coverage by over 204%, relative to a single-lens-based mmID. A theoretical link budget analysis is presented for the best- and worst case incidence angles. Using the maximum allotted 75 dBm equivalent isotropic radiated power (EIRP) in 5G/mmWave frequencies, reading ranges of 5.88 and 3.35 km are envisioned with incidence angles of 0° and 50°, respectively. To demonstrate its long-range potential for localized sensing applications, a proof-of-concept (PoC) frequency modulated continuous wave (FMCW) radar is used to range the multi-lens mmID up to 82.5 m within 6 cm of the true range even at the worst case incidence angle. This approach could potentially unlock the deployment of dense battery-less 5G-connected localizable mmID the Internet-of-Things (IoT) swarms in "Smart" digital twinning applications.